2016
DOI: 10.2215/cjn.13381215
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Urine Biomarkers in Very Low-Birth-Weight Infants

Abstract: Background and objectives Serum creatinine (SCr)-based AKI definitions have important limitations, particularly in very low-birth-weight (VLBW) neonates. Urine biomarkers may improve our ability to detect kidney damage. We assessed the association between 14 different urine biomarkers and AKI in VLBW infants.Design, setting, participants, & measurements We performed a prospective cohort study on 113 VLBW infants (weight #1200 g or ,31 weeks' gestation) admitted to a regional neonatal intensive care unit at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 20 publications
7
61
0
Order By: Relevance
“…Multivariate analysis revealed that blood creatinine level after transfusion was the best predictor of BLL% change. This goes in consonance with similar studies which proved that pathologies like acute kidney injury are best predicted by serum creatinine levels which affects up to 20% of critically ill neonates and is associated with an increased risk of mortality (15,16). On the other hand, another studies argued that although blood creatinine is the most commonly used endogenous marker for GFR, it is not the most adequate marker for the neonatal population.…”
Section: Discussionsupporting
confidence: 75%
“…Multivariate analysis revealed that blood creatinine level after transfusion was the best predictor of BLL% change. This goes in consonance with similar studies which proved that pathologies like acute kidney injury are best predicted by serum creatinine levels which affects up to 20% of critically ill neonates and is associated with an increased risk of mortality (15,16). On the other hand, another studies argued that although blood creatinine is the most commonly used endogenous marker for GFR, it is not the most adequate marker for the neonatal population.…”
Section: Discussionsupporting
confidence: 75%
“…Identification of new biomarkers predicting nephrotoxicity and enabling the early detection of AKI could improve patient outcome [139,147,400,401]. …”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…A neonatal KDIGO classification has been proposed, but serum creatinine may not be reliable as it reflects maternal creatinine and is also dependent on maturity of renal tubule function [136]. Cystatin C levels may reflect renal function better than creatinine, and various biomarkers are being investigated as a tool to detect AKI early [139,140]. The major risk factors for neonatal AKI are preterm birth, LBW, reduced nephron numbers, critical illness, and nephrotoxin exposure [58,136,141,142,143].…”
Section: Introduction To a Health Problemmentioning
confidence: 99%
“…Creatinine values were acquired using a mass spectrometry based method run in the University of Alabama at Birmingham clinical laboratory. NGAL values were acquired using a Kidney Injury Panel 5 Human kit (KIP-5) microtiter plate assay (Meso Scale Discovery, Rockville, MD, USA) [22]. Insulin levels were measured using the ACCESS ultrasensitive insulin assay kit from Beckman Coulter (Brea, CA, USA).…”
Section: Reference Methods For Methods Comparison Studiesmentioning
confidence: 99%